Rapid separation of fatty acids using a poly(vinyl alcohol) coated capillary in nonaqueous capillary electrophoresis with contactless conductivity detection. Issue 14 (21st June 2013) - Buglione, Lucia; See, Hong Heng; Hauser, Peter C.; Escarpa, Alberto; Pumera, Martin
<x xml:space="preserve">Abstract</x> The determination of fatty acids by nonaqueous CZE with capacitively coupled contactless conductivity detection was investigated. A new deoxycholate‐based BGE, which had previously been found to give significantly improved baseline stability in the determination of lipophilic organic ammonium ions, was found to be similarly beneficial for the determination of the anions. The use of a PVA‐coated capillary was required for suppression of the EOF and to obtain well reproducible results. The complete separation of 12 fatty acids could be achieved with 10 mM DOC in methanol within 6 min under optimized conditions. The PVA‐coated capillary demonstrated outstanding stability over 300 runs with no sign of depletion of the PVA layer. Method validation showed a good linearity range from 0.75 to 25 μM with correlation coefficients between 0.9949 and 0.9979. The LOD was determined as 0.5 μM for all fatty acids. The developed approach was successfully demonstrated for the separation of free fatty acids in commercial and home‐made edible oil.